Heightened Blood Pressure, but not Pulse Rate, Response to Orthostatic Challenge in Normotensive Subjects with Family History of Hypertension - Awisarita , Wiwara; Jenie, Ikhlas Muhammad (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Whether exaggerated cardiovascular response to postural changes among normotensive subjects with family history of hypertension does exist is not reported yet. Male and female normotensive subjects with (n=16) and without (n=14) hypertensive parents did postural changes from supine to standing. Systolic blood pressure, diastolic blood pressure and pulse rate were measured during supine and immediately after standing. The median value of the delta systolic blood pressure, diastolic blood pressure and pulse rate from all samples were used to classified exaggerated cardiovascular responses. The differences in the proportion of subjects with exaggerated cardiovascular responses were analysed with Chi square. P value <0.05 was considered significant. Proportion of normotensive subjects who had exaggerated systolic (≥3.5 mm Hg) or diastolic (≥2 mm Hg) blood pressure responses to postural changes were significantly higher in those with parental history of hypertension as compared to those without parental history of hypertension. Proportion of subjects who had exaggerated pulse rate (≥12 bpm) response to postural changes was not significantly different between the two groups. Normotensive young adults with family history of hypertension demonstrated heightened blood pressure, but not pulse rate, responses to orthostatic challenge from supine to standing.